A phase III randomised controlled trial of single-dose triple therapy in COPD: the IMPACT protocol - Pascoe, S; Lipson, D; Locantore, N; Barnacle, H; Brealey, N; Mohindra, R; Dransfield, M; Pavord, I; Barnes, N (European Respiratory Society, 2016)
Patients with symptomatic advanced chronic obstructive pulmonary disease (COPD) who experience recurrent exacerbations are particularly at risk of poor outcomes and present a significant burden on healthcare systems. The relative merits of treating with different inhaled combination therapies e.g. inhaled corticosteroids (ICS)/long-acting β2-agonist (LABA), LABA/long-acting muscarinic antagonists (LAMA), ICS/LABA/LAMA, in this patient group are poorly understood, as is reflected in current guidelines. The InforMing the PAthway of COPD Treatment (IMPACT) study will evaluate the efficacy and safety of fluticasone furoate (FF)/umeclidinium (UMEC)/vilanterol (VI) versus FF/VI or UMEC/VI over a 52-week treatment period. The study has been designed with a focus on understanding the comparative merits of each treatment modality in different phenotypes/endotypes.This is a phase III, randomised, double-blind, three-arm, parallel-group, global multicentre study comparing the rate of moderate and severe exacerbations between FF/UMEC/VI and FF/VI or UMEC/VI over a 52-week treatment period. The study aims to recruit 10 000 patients from approximately 1070 centres. Eligible patients are aged ≥40 years, with symptomatic advanced COPD (Global initiative for chronic Obstructive Lung Disease (GOLD) group D) and an exacerbation in the previous 12 months.The first patients were recruited to the IMPACT study (ClinicalTrials.gov: NCT02164513) in June 2014 and the anticipated completion date is July 2017.